Daily field checking list by Walter Rosene, January 28, 1940 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Robert Walker, January 28, 1940. Also notes about a foot of snow on the ground and a bird nest filled with snow. Plustek--flatbed